Desenho corpo porque vivo - Julia Gomes Panades (2007)
I Draw the Body Because I Live is the name of this research that intends to approach the artistic creation as a course of lines that draw themselves. It concerns thinking of the drawing through an expanded conception as any body made up of lines, that is to say, a drawing which does not necessarily follow the traditional techniques, categories and conceptions. Therefore, this study is centered on two main objects: the series Silhouettes, photographic actions produced by the artist Ana Mendieta; and the book The Passion According to G.H., written by Clarice Lispector. The lines of thought for this dissertation find resonances and convergences with the philosophy of Gilles Deleuze, whose conceptsconstitute fundamental tools to follow the weave of a drawing in its process of composition and dissolution.8